Parasitic protozoa and the haematological aspect of Malaysian jungle fowl (Gallus gallus spadiceus) - Zainal Abidin, B.A.H. (Indonesian Animal Sciences Society, 1995)
The presence of parasitic protozoa and haematological values of the Malaysianjungle fowl (Gallus gallus spadiceus) were determined from 41 fowls obtained from a palm oil estate . Five blood parasites (Plasmodium juxtanucleare, P. gallinaceum, Leucocytozoon sabrazesi, L. caulleryi, and Trypanosoma sp .) and four coccidia species (Eimeria mitis, E. tenella, E. maxima, andE. brunetu) were identified . It was also found that the general blood picture of the fowl was quite similar to that of the domesticated chicken. These results seem to indicate that there was no apparent relationship between the haematological values and the presence of the parasites in the blood. Key words: jungle fowl, Gallus gallus spadiceus, haematological values, parasitic protozoa